Ta’ṡīru Istikhdāmi Duolingo `ala Itqāni al-Mufradāti fī Ta`allumi al-Lugah al-`Arabiyyah lī Ṭullabi al-Madrasah aṡ-Ṡanawaiyah Muhammadiyah 2 Jenangan Ponorogo: The Effect of Using Duolingo on Vocabulary Mastery in Arabic Learning for MTs Muhammadiyah 2 Jenangan Ponorogo Students - Fitri Zakiyah; Hesti Renita; Afdhal Fikri Mirma (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2024)
The current Arabic language instruction predominantly relies on conventional methods based on textbooks, which may not fully engage students in today’s technology-driven educational landscape. Therefore, integrating modern learning tools is essential. This study investigates the implementation of the Duolingo method at MTs Muhammadiyah 2 Jenangan and analyzes its effectiveness in improving students’ proficiency in Arabic vocabulary. This study employs a quantitative approach utilizing a quasi-experimental design with two groups: an experimental group and a control group. The research population comprises 183 students, with the sample drawn from the eighth-grade cohort. Specifically, 30 students from Class VIII A were assigned to the control group, while 31 students from Class VIII B served as the experimental group. The primary instrument for data collection is a test administered as both a pre-test and a post-test. Data were analyzed using SPSS, employing several statistical procedures, including the Normality test, Wilcoxon test, Homogeneity test, and Mann-Whitney test. The results indicate that the use of the Duolingo application significantly enhances students' vocabulary acquisition in Arabic language learning, with p-values of 0.001 for both the Wilcoxon and Mann-Whitney tests, leading to the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). Keywords: Application, Arabic, Duolingo, Learning Media, Vocabulary